Nauczanie języków obcych specjalistycznych (JOS): standardy kształcenia nauczycieli a programy przygotowania do zawodu - Sowa, Magdalena (Neofilolog, 2023)
A teacher of a foreign language (FL) obtains his/her professional training during a higher education course in philology, where he/she follows a training program focused on “learning outcomes that include knowledge and skills corresponding to all the requirements of the core curriculum of the taught subject or the core curriculum of education in the profession, respectively, or the content of the classes taught” (Journal of Laws 2019, item 1450). From the this provision it should be concluded that FL teachers work in various educational institutions and with audiences of different profiles and needs, including professional ones. The article describes the scope and forms of FL/LSP teacher education in Poland, based on the results of a qualitative analysis of teacher education programs implemented in 2017–2020 at 22 Polish universities. The text presents elements of teacher specialization programs, including content specific to specialized glottodidactics at different universities/degrees. These illustrate the diversity of educational practices applied and are intended inspire the implementation of didactic solutions on a wider scale.